Use of a Melanin-Type Polymer to Improve the Selectivity of Glucose Biosensors - Rubianes, María Dolores (2003)
This paper reports the advantages of using a melanin-type polymer to improve the selectivity of glucose biosensors based on carbon paste electrodes containing Pt and glucose oxidase (GOx). The resulting bioelectrodes combine the high sensitivity of metallized electrodes with the selectivity given by the polymeric layer. They exhibit excellentperformance for glucose with a rapid response (around 10 sec per sample), a wide linear range (up to 3.0 10 2 M), low detection limits (60 mM) and a highly reproducible response (R.S.D. of 4.9%). The bioelectrodes are stable with prolonged use and almost free from the interference of easily oxidizable compounds found inbiological fluids, such as ascorbic acid (AA), uric acid (UA) and acetaminophen.